SmartBin system with waste tracking and sorting mechanism using IoT - Adi Suvarnamma (Elsevier, 2021)
Effective waste administration is one of the major environmental issues of the present time. The isolation, taking care of, transportation and transfer of waste is to be appropriately overseen in order to limit the hazard to nature. The efficient estimation of waste is best acknowledged when it is isolated. The customary method for physically isolating the waste uses exertion that is more human, time and cost. This work proposes a waste tracking system with integrated waste sorting mechanism, which is an easy and economical way to segregate and track domestic waste. It is intended to sort the domestic waste into metallic, plastic and glass categories. After segregation, the tracking system informs the server how much waste each household is producing. Along these lines, a successful framework for waste management is made helpful for recycling procedures for better environmental cleaning ecosystem with proper waste management operations.